Haemorheopheresis could block the progression of the dry form of age-related macular degeneration with soft drusen to the neovascular form - Rencová, Eva; Bláha, Milan; Studnička, Jan; Blažek, Martin; Bláha, Vladimír; Dusová, Jaroslava; Malý, Jaroslav; Kyprianou, Georgia; Vašátko, Tomáš; Langrová, Hana (Acta ophthalmologica, 2011)
PURPOSE: To evaluate the influence of haemorheopheresis on anatomical and functional findings in patients with soft-drusen maculopathy. METHODS: We investigated 29 eyes (16 patients) and randomized 25 eyes (16 controls) with soft-drusen maculopathy [soft, confluent and reticular drusen, drusenoid retinal pigment epithelium detachment (RPED)]. Each patient received a series of eight haemorheophereses (cascade filtration of 1.5 plasma volume) within 10 weeks. The patients were followed up using Early Treatment Diabetic Retinopathy Study (ETDRS) charts, optical coherence tomography, fluorescein angiography, electroretinography and measurements of pulsed ocular blood flow. RESULTS: After the procedures, there was a substantial reduction in rheologically active substances [lipoproteins, α2-macroglobulin, immunoglobulin M (IgM), fibrinogen], plasma and blood viscosity. At the 1.5-year follow-up, we noticed soft drusen absorption; reattachment of drusenoid RPED and stabilization or improvement of visual acuity occurred in 72% of patients in comparison to only 39% of patients in the control group. Full-field electroretinograms showed significantly higher scotopic activity of treated patients in comparison with the control group, and mainly insignificant differences in photopic activity between both groups. Despite the significant increase of activity in the paramacular retina in treated patients, the differences in amplitudes of multifocal electroretinography (mfERG) average responses were insignificant between groups. CONCLUSION: Haemorheopheresis seems to be capable of changing the activity of promoters of the natural course of soft-drusen maculopathy, its development and progression. Visual acuity and electrical activity of the retina can be stabilized or even improved. The therapy has been shown to be effective and safe.
Keywords: Retinal Detachment; Humans; reologie; lidé středního věku; Disease Progression; elektroretinografie; Female; Aged; optická koherentní tomografie; Macular Degeneration; odchlípení sítnice; výsledek terapie; senioři; lidé; Biomarkers; Rheology; mikrocirkulace; retinální drúzy; Plasmapheresis; makulární degenerace; Follow-Up Studies; biologické markery; ženské pohlaví; Male; Choroidal Neovascularization; Electroretinography; Middle Aged; Photography; Treatment Outcome; Aged, 80 and over; Geographic Atrophy; fotografování; senioři nad 80 let; progrese nemoci; Retinal Drusen; Tomography, Optical Coherence; mužské pohlaví; plazmaferéza; geografická atrofie; Visual Acuity; neovaskularizace choroidey; Microcirculation; zraková ostrost; následné studie